Characterisation and Pathogenicity of Aspergillus tamarii Causing Banana Fruit Rot - Latiffah Zakaria; Chai Yan Yan; Masratul Hawa Mohd; Nur Amalina Kamaruddin; Nurul Farizah Azuddin (Tropical Life Sciences Research, 2021)
Banana fruit rot is a common postharvest disease of the banana fruit. The appearance of rot symptoms on the surface of the fruits reduces the quality and marketability of banana. From rot lesions on banana fruits, three Aspergillus isolates were isolated. Based on morphological characteristics and sequences of Internal Transcribed Spacer, ?-tubulin and calmodulin, the isolates were identified as A. tamarii. Pathogenicity tests of the isolates, conducted using mycelial plugs with wounded and unwounded treatments, showed A. tamarii as the pathogen of banana fruit rot. Rot symptoms were highly severe on wounded banana fruits compared to unwounded fruits, and therefore, wounded banana fruits are more susceptible to A. tamarii infection. To the best of our knowledge, this is the first report of A. tamarii as a causal pathogen of banana fruit rot. This study indicated A. tamarii is one of postharvest rot pathogens of banana. Reput buah pisang merupakan penyakit lepas tuai yang lazim pada buah pisang. Kemunculan gejala reput pada permukaan buah mengurangkan kualiti dan kebolehpasaran buah pisang. Dari lesi reput pada buah pisang, tiga pencilan Aspergillus telah dipencilkan. Berdasarkan ciri-ciri morfologi dan jujukan Trankripsi Penjarak Dalaman (ITS), ?-tubulin dan kalmodulin, pencilan tersebut dikenal pasti sebagai A. tamarii. Ujian kepatogenan yang dilakukan menggunakan palam miselium dengan rawatan luka dan tidak luka, menunjukkan A. tamarii merupakan patogen reput buah pisang. Gejala reput amat teruk pada buah pisang yang luka berbanding buah yang tidak luka. Oleh itu, buah pisang yang luka lebih mudah dijangkiti A. tamarii. Pada pengetahuan kami, ini adalah laporan pertama A. tamarii sebagai patogen penyebab reput buah pisang. Kajian ini menunjukkan A. tamarii merupakan salah satu patogen reput pisang lepas tuai.